The Effect of Dysphagia Rehabilitation in an Acute Care Hospital - NAKANISHI, Kyoko; MATSUOKA, Mayu; WATABE, Hirotaka (The Japanese Journal of Dysphagia Rehabilitation, 2008)
【Objective】This study investigated the recovery score and the clinical application after dysphagia rehabilitation for about 9 years in an acute care hospital. In this report we try to make it clear what factors are effective to lead into recovery in an acute care hospital and point future problems.【Subjects and Methods】The subjects were 491 adult dysphagic inpatients (303 males and 188 females, average age 73.4). We measured their dysphagia severity scale (“DSS”) before and after dysphagia rehabilitation from view point of doctors of otorhinolaryngology and speech-language-hearing therapists, and defined the difference scale between the start and end of training as the recovery score. The recovery score of DSS was analyzed on the attribute of patients, the condition of dysphagia, the diagnosis of dysarthria and the training period etc. We also measured their diet status before and after dysphagia rehabilitation. The recovery score of diet status was examined along relation to the recovery score DSS.【Results】The results showed that the average recovery score DSS were 1.60, and the level with aspiration reduced to half in 36.0%. Statistics indicated that these were minor factors in the recovery score of DSS that sex, age, tracheotomy tube at the start of training and dysarthria. On the other hand, these were major factors that the cause of disease, the region of brain damaged, diet status at the start of training, the type of aspiration, aspiration pneumonia in patients' medical history, dementia, the recovery score of diet status, the period between the onset and start of training and the training period.【Discussion】 We needed to prevent aspiration pneumonia, and to choose the nutritional level based the correct assessment of dysphagia for development of effective method of dysphagia rehabilitation in an acute care hospital. It was necessary to consider the training contents according to condition of cure stage. We should provide the necessity period for recovery of dysphagia. In addition, when inpatients changed the hospitals after cure and therapy, we should cooperate with the convalescent hospital for the continuous dysphagia rehabilitation with no gap.